2023
DOI: 10.1029/2022ef003078
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Signatures of Flow Regime Alteration by Dams Across the United States

Abstract: River scientists strive to understand how streamflow regimes vary across space and time because it is fundamental to predicting the impacts of climate change and human activities on riverine ecosystems. Here we tested whether flow periodicity differs between rivers that are regulated or unregulated by large dams, and whether dominant periodicities change over time in response to dam regulation. These questions were addressed by calculating wavelet power at different timescales, ranging from 6 hr to 10 years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…We did not consider purpose of the reservoir as some of our previous publications, Chalise et al. (2021, 2023), found limited role of reservoir purpose in influencing flow alteration as it is primarily due to the limited conflicting nature of the multi‐purpose reservoirs. Synthesizing reservoir operation characteristics using data‐based methods is still at its infancy by many investigators (Ford & Sankarasubramanian, 2023; Turner et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not consider purpose of the reservoir as some of our previous publications, Chalise et al. (2021, 2023), found limited role of reservoir purpose in influencing flow alteration as it is primarily due to the limited conflicting nature of the multi‐purpose reservoirs. Synthesizing reservoir operation characteristics using data‐based methods is still at its infancy by many investigators (Ford & Sankarasubramanian, 2023; Turner et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the STHM can also be further improved for controlled basins by considering reservoir operation characteristics (Ford & Sankarasubramanian, 2023) as well as reservoir purpose. We did not consider purpose of the reservoir as some of our previous publications, Chalise et al (2021Chalise et al ( , 2023, found limited role of reservoir purpose in influencing flow alteration as it is primarily due to the limited conflicting nature of the multi-purpose reservoirs. Synthesizing reservoir operation characteristics using data-based methods is still at its infancy by many investigators (Ford & Sankarasubramanian, 2023;Turner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, dams were unimpressive predictors of flow regime according to every analysis we performed. At local and even regional scales, dams can and do fundamentally alter flow regimes (Arheimer et al., 2017; Chalise et al., 2023). However, our results suggest that at global scales, and for the majority of flow regime properties, these impacts appear to be small or difficult to measure relative to other catchment features' impacts.…”
Section: Discussionmentioning
confidence: 99%
“…In the Anthropocene, human interference with climate, land, and water is altering flow regimes, with direct impacts from dams and levees being better understood than indirect impacts imposed by land use and climatological changes (Chalise et al., 2021, 2023; Goeking & Tarboton, 2020; Zhou et al., 2015). These changes in turn impact aquatic ecosystems, human water security, and biogeochemical cycles at planetary scales (Abbott et al., 2019; Döll & Schmied, 2012; Gleeson et al., 2020; Hogeboom et al., 2020; Lin et al., 2019; Zipper et al., 2020), creating a pressing scientific challenge and opportunity to identify how climate and catchment parameters interact with direct human modifications of rivers such as dams and levees to influence river flow, and thereby shape the hydrological resilience of socioecological communities (Abbott et al., 2018; Berghuijs et al., 2019; Bunn & Arthington, 2002; Díaz et al., 2019; Harrison et al., 2018; Teixeira et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both reanalysis and observed streamflow time series are decomposed into detail and approximation components using the wavelet transform (Chalise et al, 2023). Specifically, the utilization of wavelet transform involves the rigorous mathematical deconstruction of a signal into multiple lower resolution levels (Chong et al, 2019).…”
Section: Time Series Decompositionmentioning
confidence: 99%